TRADITIONAL PUBLIC ADMINISTRATIVE SYSTEM: AN EXPOSITION in AFRICAN CONTEXT - Frank, Etim O.; Ukpere, Wilfred (Journal of Economic Development, Environment and People, 2022)
The study set out to affirm that Traditional Public Administration existed in pre-colonial Africa, specifically Nigeria. These pre-colonial administrative systems performed all the functions that is currently being executed by modern public administrative system, such as designing the best strategies for efficient delivery and the attainment of public goods. The case-study approach was adopted, in which old Oyo, Benin, Kanem Borno and Oron Kingdom amongst others were comprehensively evaluated. This approach unveiled the structures and processes through which the aforementioned empires and Kingdoms were effectively governed. The focus of this paper was to identify and analyze the structure and processes, which amounted to public administration in these empires that performed the roles which are currently being performed by modern public administration. The findings revealed that old Oyo, Benin, Kanem Borno and Oron Kingdom had standard processes for the implementation of what constituted public polices in these social entities. The successes of the administrative system accounted for the long duration of these pre-colonial states and in many cases the colonial masters relied on them, for the administration of the territories they conquered. A case in point was the ‘indirect rule’ system in Nigeria and other West Africa States, which aided the continuation of the colonial administration. The role performance in the traditional system might have been fused, however the functions of public administration were effectively carried out in these pre-colonial social entities. This exposition might have accounted for the long years of existence of these empires until internal contradictions, colonial conquests and rules resulted in their collapsed. The study through the use of qualitative data affirmed the existence of traditional public administration in Africa and Nigeria in particular. This indeed was one of the notable ‘primitive gloriana’ (glory of the primitive past) of pre-colonial Africa and Nigeria in particular, that cannot be wished away by Eurocentric scholars.